A Study on Service Quality of the Life Insurance Corporation of India - M. MAHESWARI (International Journal of Psychosocial Rehabilitation, 2020)
Insurance companies may be aware that its supremacy could get eroded by new comers unless adequate attempts are made to retain their customers. There will be an upsurge in awareness of policyholders, satisfaction of employees and policyholders and an increase in expectations that hopes and aspirations be delivered by the insurance industry. This will put an immense pressure on the insurance industry where in the industry will have to respond to it. The study focuses on policyholders’ perception of life insurance products and services offered by the LIC of India.The analysis is made on the basis of the five dimensions of service quality. Based on the analysis, it was suggested that dimensions life tangibility, empathy, and assurance s have to be developed.